2018
DOI: 10.1037/drm0000087
|View full text |Cite
|
Sign up to set email alerts
|

Pathological narcissism, dream experiences, and personality dynamics.

Abstract: This study investigated whether narcissistic grandiosity and vulnerability are related to the incidence of dreaming about persecutory themes, dream work, and dream-reality confusion and whether these relationships are modulated by superego functions, affective traits, splitting defense, somatoform distress, and hypochondria-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Eventually, we ended up with 19 documents, including data on both ANPS and Big Five personality collected on 21 independent samples, resulting in 612 distinct effect sizes representing the association between ANPS and Big Five personality scales: For all selected studies we were able to retrieve effect-size information about the association between all the ANPS behavioral scales (ANGER, CARE, FEAR, PLAY, SADNESS, and SEEKING) and Big Five traits (Agreeableness, Conscientiousness, Extraversion, Neuroticism, and Openness), except for a study by Yu 36 , which only reported information about ANPS scales and two Big Five traits (Agreeableness, Consciousness). Characteristics of selected studies are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Eventually, we ended up with 19 documents, including data on both ANPS and Big Five personality collected on 21 independent samples, resulting in 612 distinct effect sizes representing the association between ANPS and Big Five personality scales: For all selected studies we were able to retrieve effect-size information about the association between all the ANPS behavioral scales (ANGER, CARE, FEAR, PLAY, SADNESS, and SEEKING) and Big Five traits (Agreeableness, Conscientiousness, Extraversion, Neuroticism, and Openness), except for a study by Yu 36 , which only reported information about ANPS scales and two Big Five traits (Agreeableness, Consciousness). Characteristics of selected studies are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…However, other recent studies replicated earlier findings suggesting that endorsement of narcissism is related to lowered self-reported SDR (Braun et al, 2016;Jones et al, 2016;Levi & Bachar, 2019;Sedikides et al, 2004;Wu et al, 2019;Yu, 2018). Still others observed no links between endorsement of narcissism and SDR (Barelds & Dijkstra, 2010;Lyvers et al, 2019).…”
Section: -Item Socialmentioning
confidence: 50%